Deriving inherent optical properties from background color and underwater image enhancement. (15th January 2015) - Zhao, Xinwei; Jin, Tao; Qu, Song
Abstract: The colors and quality of images acquired in underwater conditions can be very poor due to the specific propagation properties of light in water, and this degradation effect is relative to the optical properties of water. We find that the background color of underwater images has a relationship with the inherent optical properties of water medium. In this paper, we propose a method of deriving inherent optical properties of water from the background color of underwater images based on an underwater image formation model. Simulations and image enhancement results show that the proposed method can effectively estimate inherent optical properties and can be used for underwater image enhancement with good performance. Highlights: The relationship between global background light and inherent optical properties is studied. The transmission of three color channels can be estimated respectively based on Dark Channel Prior and the relationship between global background light and inherent optical properties. We propose a method of single underwater image dehazing and color correction without knowing camera parameters and water optical properties in advance. Experiment in a water tank and simulations are demonstrated to verify validity of the proposed method.